2019
DOI: 10.1111/jth.14445
|View full text |Cite
|
Sign up to set email alerts
|

Obesity is associated with impaired responsiveness to once‐daily low‐dose aspirin and in vivo platelet activation

Abstract: Background:The prevalence and degree of obesity is rising worldwide, increases cardiovascular risk, modifies body composition and organ function, and potentially affects the pharmacokinetics and/or pharmacodynamics of drugs. Objectives:To investigate the pharmacodynamics of once-daily low-dose aspirin in healthy obese subjects, and to assess whether body weight (BW) and body mass index (BMI) affect the pharmacology of aspirin.Patients/Methods: Otherwise healthy, obese (BMI > 30 kg/m 2 ) subjects were studied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 44 publications
(73 reference statements)
3
42
0
2
Order By: Relevance
“…Thus, under conditions of normal thrombopoiesis, the efficacy of a short-lived drug given once daily reflects irreversible inactivation of a slowly renewable drug target (platelet COX-1) combined with an effect on bone-marrow platelet progenitors, leading to a new platelet progeny with largely non-functioning COX-1 for the vast majority of the 24-h dosing interval (Giaretta et al, 2017). However, reduced systemic bioavailability of aspirin, as may occur with some enteric-coated formulations (Maree et al, 2005) and in association with obesity (Petrucci et al, 2019), or faster renewal of platelet COX-1, as reported under conditions of altered megakaryopoiesis (Pascale et al, 2012), may shorten the duration of the antiplatelet effect of aspirin and dictate a more frequent dosing regimen (Patrono et al, 2013).…”
Section: Serum Txb2 As a Validated Index Of Platelet Cox-1 Activitymentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, under conditions of normal thrombopoiesis, the efficacy of a short-lived drug given once daily reflects irreversible inactivation of a slowly renewable drug target (platelet COX-1) combined with an effect on bone-marrow platelet progenitors, leading to a new platelet progeny with largely non-functioning COX-1 for the vast majority of the 24-h dosing interval (Giaretta et al, 2017). However, reduced systemic bioavailability of aspirin, as may occur with some enteric-coated formulations (Maree et al, 2005) and in association with obesity (Petrucci et al, 2019), or faster renewal of platelet COX-1, as reported under conditions of altered megakaryopoiesis (Pascale et al, 2012), may shorten the duration of the antiplatelet effect of aspirin and dictate a more frequent dosing regimen (Patrono et al, 2013).…”
Section: Serum Txb2 As a Validated Index Of Platelet Cox-1 Activitymentioning
confidence: 99%
“…Obesity is associated with biochemical evidence of persistently enhanced platelet activation (Davì et al, 2002; Petrucci et al, 2019) and high risk of atherothrombotic complications (reviewed by Rocca et al, 2018). Recently, Rothwell et al (2018) analyzed individual data of 117,279 subjects recruited into 10 primary prevention trials and reported that low doses of aspirin (75–100 mg) were only effective in preventing major vascular events in subjects with body weight lower than 70 kg, and had no benefit in the vast majority of men and nearly 50% of all women weighing 70 kg or more.…”
Section: Serum Txb2 As a Validated Index Of Platelet Cox-1 Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, we rely on consensus expert advice to guide these clinical scenarios, for example, the ESC Working Group on Thrombosis consensus statement on aspirin and obesity, which advices that while limited data is available on aspirin dosing in people with a body mass index (BMI) above 40 kg/m 2 , it is reasonable to double the daily low dose of aspirin or give a twice-daily low dose. Recent work has shown a higher residual TXB 2 in moderate-to-severe obese people in contrast to non-obese subjects in their response to once-daily low dose aspirin, and in fact, increasing residual serum TXB 2 was found to be exponentially correlated with BMI and body weight in 100 subjects taking standard low-dose aspirin (100 mg once daily) [50].…”
Section: Optimising the Aspirin Dose And Dosing Regimenmentioning
confidence: 96%